Evaluation of marginal bone level after implant placement and before loading, by digital radiography - Sapkota, Binam; Upadhyaya, Chandan; Rimal, Ujjwal; Mahanta, Swagat Kumar (Journal of Kathmandu Medical College, 2022)
Background: Marginal bone loss around dental implant is one of the criteria for evaluating implant success. Objectives: To evaluate the marginal bone loss around dental implants using digital radiographs and to determine correlation of mesial and distal bone loss around dental implants with gender and location in either arch in a period of 3-6 months after placement and before prosthetic loading. Methods: An analytical study was undertaken from July 2021 till December 2021, after ethical clearance, in 18 patients on whom 23 implants had been placed at Dhulikhel hospital. After implant placement first radiograph was taken by CE 0297 size 2 PSP plate and Carestream (CS2100) intraoral periapical radiograph machine using paralleling technique (XcpRinn Device) and second at 3-6 months later. The radiographs were viewed using image viewer software (Vistasoft2.0.1) to calculate the bone level. Calculating the difference in bone level at zero month and at 3-6 months gave us the amount of bone loss which was entered in Excel sheet and transferred to SPSS v.22 for analysis and student unpaired-t test was used.Results: The mean bone loss was 0.27 ± 0.2 mm on mesial aspect and 0.13 ± 0.3 mm on distal aspect at the end of the study period. No statistically significant bone loss in relation to gender and location of implant placement was found. Conclusion: Within the limitation of the study, no significant difference was found in the mesial and distal aspect of bone loss around dental implant when compared with different parameters.